Dealing with balance of payments adjustment problems in Barbados : a conceptual perspective - Francis, Brian M. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2005)
Addresses two key questions viz. Is there a solution to the current balance of payments problems being experienced by Barbados? Second, If there is a solution, what is it?